2008
DOI: 10.1136/jech.2006.057166
|View full text |Cite
|
Sign up to set email alerts
|

Trends in socioeconomic mortality inequalities in a southern European urban setting at the turn of the 21st century

Abstract: Relative inequalities in total mortality by sex in Barcelona did not change during the 12 years studied, whereas absolute inequalities tended to decrease in men. Our study fills an important gap in southern Europe and Spanish literature on trends during this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 41 publications
10
29
0
1
Order By: Relevance
“…A similar resultabsolute decrease, relative stability-was observed for Barcelona (Borrell et al 2008), whereas all other available studies reported a further increase in relative inequality (see introduction).…”
Section: Comparison With Results From Other Countries In the 1990ssupporting
confidence: 49%
See 1 more Smart Citation
“…A similar resultabsolute decrease, relative stability-was observed for Barcelona (Borrell et al 2008), whereas all other available studies reported a further increase in relative inequality (see introduction).…”
Section: Comparison With Results From Other Countries In the 1990ssupporting
confidence: 49%
“…For the city of Rome an increase in relative differentials during the 1990s and a stabilization at the very end of the 20 th century was reported (Cesaroni et al 2006), whereas for Barcelona relative stability was observed during the entire decade (Borrell et al 2008). Fawcett et al (2005) suggest that in the first half of the 1990s socio-economic mortality differentials at working ages were further increasing also in Norway and Finland, though for females the gap in circulatory disease mortality was not further widening.…”
Section: Introductionmentioning
confidence: 95%
“…10 However, many studies have also observed greater inequalities among women than among men. 4,14 Some studies find them at individual level, 8,10,12,29,30,32 others at area level (ecological studies), 35,38,39,43,50,51 and lastly, there are some multilevel studies, 15,16,20 which have found such inequalities at area level, independently of the individual's socioeconomic level. However, few studies have discussed the possible causes of these differences between the sexes.…”
Section: Trends In Socioeconomic Inequalities In Ihd Mortalitymentioning
confidence: 99%
“…Studies of trends at individual level performed in different European countries have found that the socioeconomic inequalities in IHD mortality tend to increase with time in both sexes. 29,30,32,54 Few ecological studies have analyzed the evolution over time of these inequalities. In the majority of them, increases in socioeconomic inequalities are observed in both sexes.…”
Section: Trends In Socioeconomic Inequalities In Ihd Mortalitymentioning
confidence: 99%
See 1 more Smart Citation